2018
DOI: 10.1101/382127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon monoxide, a retrograde messenger generated in post-synaptic mushroom body neurons evokes non-canonical dopamine release

Abstract: ABSTRACTDopaminergic neurons innervate extensive areas of the brain and release dopamine (DA) onto a wide range of target neurons. However, DA release is also precisely regulated, and in Drosophila, DA is released specifically onto mushroom body (MB) neurons, which have been coincidentally activated by cholinergic and glutamatergic inputs. The mechanism for this precise release has been unclear. Here we found that coincidentally activated MB neurons g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 112 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Most of the previous studies investigating the associative learning circuit ex vivo have focused on mapping connectivity (Cohn et al, 2015;Barnstedt et al, 2016;Felsenberg et al, 2017;Felsenberg et al, 2018;Zhao et al, 2018) or characterizing a specific biochemical pathway (Tomchik and Davis, 2009;Handler et al, 2019;Ueno et al, 2020). Only a few ex vivo studies (Wang et al, 2008;Ueno et al, 2013;Suzuki-Sawano et al, 2017;Ueno et al, 2017) have focused on understanding MB circuit logic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies investigating the associative learning circuit ex vivo have focused on mapping connectivity (Cohn et al, 2015;Barnstedt et al, 2016;Felsenberg et al, 2017;Felsenberg et al, 2018;Zhao et al, 2018) or characterizing a specific biochemical pathway (Tomchik and Davis, 2009;Handler et al, 2019;Ueno et al, 2020). Only a few ex vivo studies (Wang et al, 2008;Ueno et al, 2013;Suzuki-Sawano et al, 2017;Ueno et al, 2017) have focused on understanding MB circuit logic.…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanistic studies employing the LTE paradigm reported no dopamine release after US pathway stimulation alone. Strong dopamine release was only seen after coincident activation of both the CS and the US pathways, and it was concluded that dopamine release is downstream of the CS+US coincidence and does not encode the primary US information (Ueno et al, 2017;Ueno et al, 2020). To directly address this discrepancy, we expressed a G-protein-coupled receptor-activation-based dopamine sensor (GRABDA) (Sun et al, 2020) in the KCs.…”
Section: Dopamine Replaces the Artificial Us Stimulus But Does Not Re...mentioning
confidence: 99%